KETIDAKSIAPAN PSIKOLOGIS PASANGAN DISPENSASI NIKAH SEBAGAI FAKTOR PERCERAIAN: ANALISIS YURIDIS DI PENGADILAN AGAMA SUWAWA - Syifa Nurlita Tavadjio; Nur Mohammad Kasim; Nurul Fazri Elfikri (At-Tanwir Law Review, 2026)
Marriage dispensation is often granted on the grounds of pregnancy and socialinteraction factors, even though the individuals involved are not yetpsychologically ready. This study aims to analyze the psychologicalunpreparedness of couples who marry through dispensation as a contributingfactor to divorce, as well as to identify the forms of legal protection available tothem. The research employs a juridical-empirical method, utilizing primary dataobtained from interviews at the Suwawa Religious Court and secondary dataderived from legislation and relevant literature. The findings indicate thatdivorces among dispensation marriage couples are largely caused by emotional,cognitive, and economic immaturity. Forms of legal protection for childreninclude preventive protection through marriage age regulations, repressiveprotection through law enforcement mechanisms, and rehabilitative protectionthrough recovery efforts. In conclusion, marriage dispensation is closelycorrelated with divorce; therefore, strengthening regulations, conductingcomprehensive psychological assessments, enhancing inter-agency coordination,and fostering parental guidance and religious values are essential.